2020
DOI: 10.1136/archdischild-2020-319990
|View full text |Cite
|
Sign up to set email alerts
|

Danish premature birth rates during the COVID-19 lockdown

Abstract: To explore the impact of COVID-19 lockdown on premature birth rates in Denmark, a nationwide register-based prevalence proportion study was conducted on all 31 180 live singleton infants born in Denmark between 12 March and 14 April during 2015–2020.The distribution of gestational ages (GAs) was significantly different (p=0.004) during the lockdown period compared with the previous 5 years and was driven by a significantly lower rate of extremely premature children during the lockdown compared with the corresp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
335
8
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(383 citation statements)
references
References 5 publications
20
335
8
4
Order By: Relevance
“…These results at least suggest that the number of high-risk newborns requiring intensive neonatal care was decreased during this outbreak, even though the possibility of the hospitals' incapability of providing intensive neonatal care remains. Combined with consistent findings in three early reports in Europe, [1][2][3] our study reinforces the hypothesis that changes in lifestyles at the maternal and community levels during the COVID-19 outbreak (movement restriction and the increased focus on infection prevention measures) might have had a positive secondary effect on maternal or fetal conditions, possibly through reduced rates of intrauterine infections or alleviated maternal physical stress. Our findings reappraise the importance of arranging the prenatal living environment to protect newborns and mothers.…”
Section: Discussionsupporting
confidence: 91%
“…These results at least suggest that the number of high-risk newborns requiring intensive neonatal care was decreased during this outbreak, even though the possibility of the hospitals' incapability of providing intensive neonatal care remains. Combined with consistent findings in three early reports in Europe, [1][2][3] our study reinforces the hypothesis that changes in lifestyles at the maternal and community levels during the COVID-19 outbreak (movement restriction and the increased focus on infection prevention measures) might have had a positive secondary effect on maternal or fetal conditions, possibly through reduced rates of intrauterine infections or alleviated maternal physical stress. Our findings reappraise the importance of arranging the prenatal living environment to protect newborns and mothers.…”
Section: Discussionsupporting
confidence: 91%
“…Studies from the Netherlands, Denmark, Ireland, Italy, and Japan demonstrated a reduction in preterm births following the implementation of lockdown measures. [2][3][4][5][6] In contrast, studies from the United States in California and Philadelphia reported no significant change in preterm births after lockdown. [7,8] In this NYC study, we observed comparable rates in prematurity and NICU admissions after the implementation of lockdown measures when compared to those of the same time period in previous years.…”
Section: Discussionmentioning
confidence: 94%
“…Several reports linked COVID-19 lockdown measures to reduced rates of prematurity, providing possible mechanisms for prematurity prevention. [2][3][4][5][6] To date, this link has not been assessed in NYC, one of the hardest hit and most populous, diverse cities in the United States. Furthermore, neonatal intensive care unit (NICU) admissions, which are related but not exclusively modified by prematurity rates, may also be impacted by lockdown measures.…”
Section: Introductionmentioning
confidence: 99%
“…In maternity care however, consequences of the imposed restrictions have been mixed. Early reports from some countries suggest that although stillbirth rates increased (3)(4)(5), rates of preterm birth actually decreased (5)(6)(7)(8)(9). It is not clear if there is a similar trend in Australia.…”
Section: Introductionmentioning
confidence: 99%